Essential MATLAB for engineers and scientists - Hahn, Brian D.; Valentine, Daniel T., 1946- (Engineering professional collection, 2013)
This book provides a concise, balanced overview of the functionality in MATLAB®. It facilitates independent learning with coverage of both the fundamentals and applications in two parts. The essentials of MATLAB are illustrated throughout with many examples from a wide range of familiar scientific and engineering areas, as well as from everyday life. This is an ideal textbook for a first course on MATLAB or an engineering problem solving course using MATLAB, as well as a self-learning tutorial for professionals and students who are expected to learn and apply MATLAB themselves.